Parasite clearance rates in Upper Myanmar indicate a distinctive artemisinin resistance phenotype: a therapeutic efficacy study. (December 2016) - Tun, Kyaw; Jeeyapant, Atthanee; Imwong, Mallika; Thein, Min; Aung, Sai; Hlaing, Tin; Yuentrakul, Prayoon; Promnarate, Cholrawee; Dhorda, Mehul; Woodrow, Charles; Dondorp, Arjen; Ashley, Elizabeth; et al.
Abstract Background Artemisinin resistance inPlasmodium falciparum extends across Southeast Asia where it is associated with worsening partner drug resistance and a decline in the efficacy of frontline artemisinin-based combination therapy. Dihydroartemisinin-piperaquine (DP) is an essential component of preventive and curative treatment in the region, but its therapeutic efficacy has fallen in Cambodia. Methods A prospective clinical and parasitological evaluation of DP was conducted at two sites in Upper Myanmar between August 2013 and December 2014, enrolling 116 patients with acute uncomplicated falciparum malaria. Patients received DP orally for 3 days together with primaquine 0.25 mg/kg on admission. Parasite clearance half-lives based on 6 hourly blood smears, and day 42 therapeutic responses were assessed as well as parasite K13 genotypes. Results Median parasite clearance half-life was prolonged, and clearance half-life was greater than 5 h in 21 % of patients. Delayed parasite clearance was significantly associated with mutations in the propeller region of the parasitek13 gene. Thek13 F446I mutation was found in 25.4 % of infections and was associated with a median clearance half-life of 4.7 h compared with 2.7 h for infections withoutk13 mutations (p < 0.001). There were no failures after 42 days of follow-up, although 18 % of patients had persistent parasitaemia on day 3. Conclusion The dominantk13 mutation observed in Upper Myanmar, F446I, appears to be associated with an intermediate rate of parasite clearance compared to other common mutations described elsewhere in the Greater Mekong Subregion. Discerning this phenotype requires relatively detailed clearance measurements, highlighting the importance of methodology in assessing artemisinin resistance.